Uptake of Postpartum Long-Acting Reversible Contraception: The Impact of Timing and Practice Patterns [29J]. (May 2020) - Corbin, Kaitlin; Miller, Hayley; Bates, Paige; Lerma, Klaira; Noon, Brigit; Shaw, Kate A.
Abstract : INTRODUCTION: Uptake of long-acting reversible contraception (LARC) postpartum is impacted by differences in clinical practices, contraceptive counseling, postpartum follow-up and temporary Medicaid coverage. We sought to determine whether differences in inpatient provision influence uptake of preferred LARC by 8-weeks postpartum. METHODS: We performed an IRB approved, retrospective cohort study of all deliveries after 24 weeks gestation in two distinct practice groups at a single academic center in 2016: Practice A routinely offers initiation of intrauterine devices (IUDs) and contraceptive implants prior to hospital discharge; Practice B only routinely offers implants. We collected demographic information, documented postpartum contraception preference and LARC uptake by 8-weeks postpartum. RESULTS: We included all deliveries from Practice A (n=878) and Practice B (n=739). Patients from B were younger, Hispanic, publicly insured multiparas with a term, vaginal delivery. At discharge, more from B desired LARC (A: 27.2%, B: 39.2%; P<.001), but more from A desiring LARC initiated prior to discharge (A: 64.9%, B: 39.4%; P<.001). Postpartum follow-up was higher for B (A: 74.5%, B: 83.9%; P<.001), but by 8 weeks, uptake of desired IUD was higher for A (A: 72.9%, B: 51.6%, P<.001), with the majority placed inpatient for A (86.1% vs 10.6%; P<.001). Implant uptake by 8 weeks was similar (A: 86.3%, B: 90.4%; P= .41), with the majority placed inpatient (A: 72.5%, B: 69.2%; P<.001). CONCLUSION: Routine access to immediate postpartum IUD placement results in significantly increased uptake of desired IUD by 8-weeks postpartum, supporting provision of immediate postpartum LARC. Future efforts should focus on understanding if the option of immediate postpartum IUD placement influences contraceptive counseling, patient preferences and uptake.